2019
DOI: 10.1093/geront/gnz149
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Combined Cognitive and Physical Interventions to Enhance Functioning in Older Adults With Mild Cognitive Impairment: A Systematic Review of Randomized Controlled Trials

Abstract: Background and Objectives Cognitive training delivered in conjunction with physical activity, may help to optimize aging and delay or prevent dementia in individuals with mild cognitive impairment (MCI). However, their efficacy is less well studied compared to pharmaceutical treatments. This systematic review synthesizes the emerging evidence on combined cognitive-physical interventions for enhancing functioning in older adults with MCI, with implications for practice and research. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 44 publications
5
48
0
Order By: Relevance
“…We also clarified the relationship between retention patterns and outcomes from MCI through a 4-year follow-up. The MCI to NC reversion rate ranges from 10% to 50%, depending on the follow-up period and MCI subtype [6,7]. In a previous study with a study population similar to ours and follow-up, the reversion rate was 35% [30], which is similar to the 30.9% rate in our study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We also clarified the relationship between retention patterns and outcomes from MCI through a 4-year follow-up. The MCI to NC reversion rate ranges from 10% to 50%, depending on the follow-up period and MCI subtype [6,7]. In a previous study with a study population similar to ours and follow-up, the reversion rate was 35% [30], which is similar to the 30.9% rate in our study.…”
Section: Discussionsupporting
confidence: 87%
“…Individuals with MCI, or those who experience impairment across one or more cognitive domains (e.g., memory, language, thinking, and judgment), beyond that expected for age, are at an increased risk of progressing to AD and other types of dementias [3][4][5]. This is concerning, given that up to 20% of people over the age of 65 experience MCI [6,7]. Various factors have been related to the onset of dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic reviews have supported the efficacy of cognitive training (Gavelin et al, 2020; Hill et al, 2017; Lampit et al, 2014; Leung et al, 2015) and physical exercise (Falck et al, 2019; Northey et al, 2018) on cognitive performance in older adults with and without cognitive impairment. These interventions have also been recommended in clinical practice guidelines (e.g., for mild cognitive impairment; Petersen et al, 2018) and, increasingly, the possibility of combining physical exercise with cognitively challenging activities has been highlighted as a way to maintain both cognitive and physical health (Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These therapeutic effects of Baduanjin were similar to those of other physical exercises 36 and combined cognitive and physical interventions. 37…”
Section: Discussionmentioning
confidence: 99%
“…These therapeutic effects of Baduanjin were similar to those of other physical exercises 36 and combined cognitive and physical interventions. 37 Meta-analysis of the cerebrospinal fluid indexes reported by three studies suggested that Baduanjin may improve cognitive function by reducing Tau protein levels and increasing Aβ 1-42 levels in the cerebrospinal fluid. Some studies have shown that biomarkers such as Tau protein and Aβ 1-42 are closely related to cognitive function; for example, a high Tau/Aβ 1-42 ratio is associated with worse performance on cognition and memory tests, and plays an important role in the early detection and identification of early Alzheimer disease.…”
Section: Discussionmentioning
confidence: 99%